2018
DOI: 10.1161/hypertensionaha.117.09906
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclooxygenase-2 Selectively Controls Renal Blood Flow Through a Novel PPARβ/δ-Dependent Vasodilator Pathway

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
2
21
1
Order By: Relevance
“…Also, one of these reports further showed that the endothelial muscarinic agonist ACh evoked COX‐mediated contractile response, 50 similar to results obtained in renal arteries here or previously 22 . Moreover, there are reports including one on mice showing that PGI 2 or PGI 2 analogues evoke intrarenal vasoconstriction in vivo or ex vivo 21,51‐54 . These facts favor a general vasoconstrictor effect of PGI 2 via TP and EP3 on the mouse renal vasculature as suggested by findings of the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, one of these reports further showed that the endothelial muscarinic agonist ACh evoked COX‐mediated contractile response, 50 similar to results obtained in renal arteries here or previously 22 . Moreover, there are reports including one on mice showing that PGI 2 or PGI 2 analogues evoke intrarenal vasoconstriction in vivo or ex vivo 21,51‐54 . These facts favor a general vasoconstrictor effect of PGI 2 via TP and EP3 on the mouse renal vasculature as suggested by findings of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…22 Moreover, there are reports including one on mice showing that PGI 2 or PGI 2 analogues evoke intrarenal vasoconstriction in vivo or ex vivo. 21,[51][52][53][54] These facts favor a general vasoconstrictor effect of PGI 2 via TP and EP3 on the mouse renal vasculature as suggested by findings of the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Work from our group and of others has shown that activation of PPARβ can also explain some of the acute effects of prostacyclin in platelets and blood vessels (Ali et al, ; Baron et al, ; Harrington et al, ; Li et al, ; Kirkby et al, ). Initially, this was a surprising discovery as PPARβ was thought to be a pathway that regulates gene induction rather than acute signalling events; however, now we know that PPARβ activation leads to the engagement of both genomic and non‐genomic pathways (Mitchell et al, ).…”
Section: Role Of Cox‐2 In Cardiovascular Protection and The Cardiovasmentioning
confidence: 87%
“…Inhibition of intracellular calcium mobilization in platelets and vascular smooth muscle cells leads to attenuated aggregation response [ 60 ] and vessel dilation, respectively, both of which contribute to the anti-thrombotic effects of PGI 2 . Like the surface IP receptor, the intracellular receptor PPARβ/ δ has also been reported to regulate signaling events during platelet activation and vessel dilation [ [61] , [62] , [63] ].…”
Section: Roles Of Mas Receptor Pgi 2 and Sirt1 mentioning
confidence: 99%